Impact of red blood cell distribution width on non-cardiac mortality in patients with acute decompensated heart failure with preserved ejection fraction. Issue 6 (December 2017) - Imai, Ryo; Uemura, Yusuke; Okumura, Takahiro; Takemoto, Kenji; Uchikawa, Tomohiro; Koyasu, Masayoshi; Ishikawa, Shinji; Iwamiya, Satoshi; Ozaki, Yuta; Shibata, Rei; Watarai, Masato; Murohara, Toyoaki
Abstract: Background: The prognostic impact of red blood cell distribution width (RDW) on adverse outcomes in patients with heart failure with preserved ejection fraction (HFpEF) is unclear. We investigated the association between RDW values at admission and long-term prognosis in patients with acute decompensated HFpEF. Methods: The present study enrolled 278 consecutive patients with acute decompensated HFpEF, whose RDW levels were measured at admission. We divided enrolled patients into 2 groups according to RDW value and investigated the association between RDW and patients' mortality. Results: A Kaplan–Meier analysis demonstrated that patients with higher RDW levels had significantly higher all-cause and non-cardiac mortality, but not cardiac-based mortality, than did patients with lower RDW levels. A multivariate Cox regression analysis revealed that RDW levels were independently correlated with all-cause and non-cardiac mortality after adjusting for other risk factors, including age, brain natriuretic peptide, hemoglobin, and Charlson comorbidity index score. In a receiver-operating curve analysis, the cut-off value to maximize the prognostic impact of RDW on mortality was 15.2%. The evaluation of RDW and other prognostic factors improved their predictive value for both all-cause and non-cardiac mortality. Conclusions: The current study demonstrated that RDW levels at admission independently predict poor outcomes because of non-cardiac events in patients with acute decompensated HFpEF. Evaluation of RDW could provide useful information for the long-term prognosis of HFpEF.